PERLINDUNGAN HUKUM BAGI PT. DIGITAL COMMERCE INDONESIA (KONSUMEN ANTARA) ATAS WANPRESTASI PENGIRIMAN BARANG OLEH PT. ANDIARTA MUZIZAT - Astika, Mariana; Subekti, Subekti; Ayuningtiyas, Fitri; Prawesthi, Wahyu (Gapenas Publisher, 2025)
The development of digital commerce in Indonesia has made freight forwarding services a strategic sector in supporting the smooth distribution of products. However, delivery defaults often cause significant losses, not only for end consumers but also for intermediate consumers who act as intermediaries in the distribution chain. This study stems from the urgency of legal protection for intermediate consumers, which is still rarely discussed in consumer protection law studies. The main questions asked are how logistics service providers are legally responsible for delivery defaults and what form of legal protection is available for intermediate consumers within the framework of applicable regulations. This study uses a normative legal method with a legislative approach, a conceptual approach, and a case approach. The primary legal materials are laws and regulations such as the Civil Code, UUPK, and ITE Law, as well as South Jakarta District Court Decision Number 151/Pdt.G/2020/PN.Jak.Sel. Secondary legal materials are literature and academic publications, while tertiary legal materials are legal dictionaries and encyclopaedias. The analysis was conducted qualitatively by examining legal norms and their relevance to specific cases. The results of the study show that PT. Andiarta Muzizat was proven to have committed a breach of contract by not fulfilling its obligation to deliver goods based on COD, which resulted in material losses of Rp13.3 billion and immaterial losses in the form of a decline in the reputation of PT. Digital Commerce Indonesia. The court's decision affirmed the obligation of business actors to compensate for losses based on Article 1243 of the Civil Code and the principle of pacta sunt servanda. These findings demonstrate the need to strengthen legal protection for vulnerable consumers. The conclusion of the study emphasises that consumer protection must include consumers through the strengthening of regulations, supervision, and effective dispute resolution mechanisms. Further studies are recommended to explore the effectiveness of non-litigation settlements through the BPSK and the integration of electronic contracts in digital consumer protection.